Monte Carlo simulation study of reflection electron energy loss spectroscopy of an Fe/Si overlayer sample. (23rd July 2020) - Da, Bo; Yang, Lihao; Liu, Jiangwei; Li, Yonggang; Mao, Shifeng; Ding, Zejun
Abstract : Reflection electron energy loss spectroscopy (REELS) has been used to study the optical and electronic properties of semi‐infinite solid samples, aided by a theoretical model of the interaction between electrons and a solid. However, REELS has not been used to its full capacity in studying nanomaterial samples because of the difficulty in modeling the electron interaction with a layered nanostructure. In this study, we present a numerical calculation result on the spatially varying inelastic mean free path for a sample comprising an Fe layer of varying thickness on an Si substrate. Furthermore, a Monte Carlo model for electron interaction with this Fe‐Si layered structure sample is built based on this inelastic scattering cross section and used to reproduce the REELS spectra of Fe‐Si layered structures. The simulated spectra of the sample with varying Fe layer thickness on top of a Si substrate were compared with the experimental spectra. This comparison clearly identifies that the Fe layer remaining on top of the experimental Si substrate after Ar + beam sputtering is in the form of a homogeneous mixed layer, where the Fe/Si interface excitation is absent in the experimental spectra owing to pulverization of the Fe/Si interface during the Ar + sputtering process.